Factors Influencing Difficulties of Learning Economics (Study in Students of Kudus District High School) - Pertiwi, Raras Sukma; Khafid, Muhammad; Setyadharma, Andryan (Universitas Negeri Semarang, 2019)
Teaching and learning activities have an important role so that education can run well. Basically teaching and learning activities lead to the achievement of student learning outcomes. Learning outcomes achieved by students can be used as a reference in knowing students' abilities and as a correction whether students are still experiencing difficulties in learning. The purpose of this method was to analyze and identify the learning difficulties of the students of Kudus District High School. Students' perceptions regarding teacher teaching methods, learning independence, and learning interest are used to measure learning difficulties. This method used a quantitative approach. The study population amounted to 1033 students and the sample amounted to 233 students. The sampling technique used is proportional random sampling. The method of data collection was using a questionnaire. The method of data analysis uses descriptive analysis and path analysis. The results of path analysis showed the direct influence of students' perceptions regarding teacher teaching methods on learning interest, direct influence of students' perceptions regarding teacher teaching methods on learning difficulties, direct influence of learning independence on learning difficulties, direct influence of learning interest on learning difficulties. Indirectly students' perceptions regarding teacher teaching methods influence the difficulty of learning through interest in learning.